COVID-19 and coinfection with Clostridioides (Clostridium) difficile in an infant with gastrointestinal manifestation - Oba,Jane (2020)
ABSTRACT We report the clinical case of an infant with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection with gastrointestinal signs and symptoms, predominantly vomiting. The patient also had colic, poor feeding, mild diarrhea and mild rhinorrhea without fever. The child had evidence of altered coagulation, increased interleukin 10, moderate dehydration and she was admitted to the pediatric intensive care unit. Simultaneously, the patient was diagnosed as Clostridioides difficile infection, which possibly may have facilitated the persistence of SARS-CoV-2 in feces, for more than 27 days, even after the nasopharyngeal test turned negative. This coinfection might exacerbate the gastrointestinal signs and symptoms and increased the possibility of fecal-oral transmission of SARS-CoV-2 and Clostridioides . The patient was breastfed and received complementary infant formula, hydrated with intravenous fluid, and was discharged without complications, 4 days after admission.